A Composite Fiber Separator with Reversible Thermal Shutdown for Safety of Lithium‐Ion Batteries. Issue 9 (7th July 2022) - Gao, Tingting; Tian, Peng; Yang, Yongyu; Xu, Qianjin; Pang, Hongchang; Ye, Junwei; Ning, Guiling
Abstract : Commercial lithium‐ion battery separators suffer from low porosity, inferior wettability, and poor thermal stability. It is essential to develop separators with better thermal stability and electrolyte uptake to improve the performance and safety of lithium‐ion batteries. Herein, the belt‐like boehmite (AA‐BM) is synthesized and used in the separators as inorganic reinforcing material. Electrospinning technology is utilized to prepare multifunctional AA‐BM/polyacrylonitrile (PAN) separators. As a result, the AA‐BM/PAN separators demonstrate high porosity, low contact angle, excessive electrolyte uptake, and excellent thermal shrinkage. The AA‐BM/PAN separators are assembled into half‐cells (LiFePO4 //separator//Li). AA‐BM/PAN separators show superb thermal stability at high temperatures and excellent reversible thermal shutdown performance. In addition, Li//Li batteries show that the PAN separators of boehmite compound can effectively inhibit the growth of lithium dendrite and improve the safety of batteries. Abstract : The belt‐like boehmite (AA‐BM)/polyacrylonitrile (PAN) composite fiber separator is fabricated by compounding the boehmite nanobelt with PAN via electrospinning. The separator exhibits superb physical, chemical, and electrochemical properties. Furthermore, it shows excellent electrochemical stability and thermal shutdown performance at 150 °C. In addition, this separator can inhibit the growth of lithium dendrites.